PEMBERDAYAAN MASYARAKAT BERBASIS KEARIFAN LOKAL DI ERA DIGITALISASI MELALUI PELATIHAN BATIK ECOPRINT DI DESA KEDUNGMLATI - Siti Dinarti; Esty Saraswati Nur Hartiningrum; Anisa Nur Aini Fadhila Wati; Ais Arum Pratiwi (STKIP PGRI Sidoarjo, 2024)
This service activity was carried out in Kedungmlati Village, Kesamben District, Jombang Regency, East Java. In the area there are many leaves that have high leaf green substances and are potential that can be developed for the empowerment of the Kedungmlati village community. The community can utilise the natural resources around them as materials as a form of new business opportunities, one of which is the development of ecoprint batik typical of Kedungmlati. Community empowerment with nature-friendly batik skills, namely ecoprint, can reduce textile waste. Ecoprint is a technique of giving patterns to fabric media using natural materials. The fabric can be processed again into multipurpose items such as bags. Marketing of ecoprint results is done through marketplaces and social media. This service activity was carried out in the form of training in making ecoprint batik, training in making bags from ecoprint batik, and digital marketing training using marketplace applications. The targets of this activity are PKK mothers who mostly have a side business as a celebration bag tailor. The method used in this community service activity is community-based participatory action which is divided into three stages, namely planning, implementation and evaluation. During the training activities, the making of ecoprint batik went well. The participants were very enthusiastic when practising it. The results of this service are very important to be developed as a form of community skills development effort so that it can be used as an alternative effort to improve the economy of Kedungmlati Village.